Phylogeography of Francisella tularensis subspecies holarctica and epidemiology of tularemia in Switzerland - Schütz, Sara Doina; Liechti, Nicole; Altpeter, Ekkehardt; Labutin, Anton; Wütrich, Tsering; Schmidt, Kristina Maria; Buettcher, Michael; Moser, Michel; Bruggmann, Rémy; Wittwer, Matthias (Frontiers in Microbiology, 2023)
Tularemia, an endemic disease that mainly affects wild animals and humans, is caused by Francisella tularensis subsp. holarctica (Fth) in Switzerland. The Swiss Fth population consist of multiple different subclades which are distributed throughout the country. The aim of this study is to characterize the genetic diversity of Fth in Switzerland and to describe the phylogeographic relationship of isolates by single nucleotide polymorphism (SNP) analysis. This analysis is combined with human surveillance data from reported cases over the last 10 years and in vitro and in silico antibiotic resistance tests to provide insight into the epidemiology of tularemia in Switzerland. We sequenced the whole genomes of 52 Fth strains of human or tick origin collected in Switzerland between 2009 and 2022 and analyzed together with all publicly available sequencing data of Swiss and European Fth. Next, we performed a preliminary classification with the established canonical single nucleotide polymorphism nomenclature. Furthermore, we tested 20 isolates from all main Swiss clades for antimicrobial susceptibility against a panel of antimicrobial agents. All 52 sequenced isolates from Switzerland belong to major clade B.6, specifically subclades B.45 and B.46,, previously described in Western Europe. We were able to accurately reconstruct the population structure according to the global phylogenetic framework. No resistance to clinically recommended antibiotics could be identified in vitro or in silico in the western B.6 strains.